2003
DOI: 10.2166/wst.2003.0089
|View full text |Cite
|
Sign up to set email alerts
|

Mixing and its impact on faecal coliform removal in a stabilisation pond

Abstract: Faecal coliform removal in stabilisation ponds is highly dependent on shortest water retention times. Tracer tests have been performed in a 3,300 m2 and 1.0 m deep pond, located in Southern France, to measure the retention times and bring light on the main influencing factors and mechanisms. Tracer concentrations were monitored at the outlet and 60 locations within the pond--at the surface, mid depth and the bottom of the water column. Pond water temperatures were measured at different depths and locations, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…Consistent cycles of thermal stratification and night-time natural convection in maturation ponds have been reported (e.g. Gu and Stefan, 1995;Brissaud et al, 2003;Dahl et al, 2017a,b). Modelling and experimental evidence reported that the combination of thermal stratification and vertically attenuated sunlight in the water column is the cause for greater die-off in the near surface region of the water column during the day (Brissaud et al, 2003;Dahl et al, 2017a,b).…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Consistent cycles of thermal stratification and night-time natural convection in maturation ponds have been reported (e.g. Gu and Stefan, 1995;Brissaud et al, 2003;Dahl et al, 2017a,b). Modelling and experimental evidence reported that the combination of thermal stratification and vertically attenuated sunlight in the water column is the cause for greater die-off in the near surface region of the water column during the day (Brissaud et al, 2003;Dahl et al, 2017a,b).…”
Section: Introductionsupporting
confidence: 64%
“…Gu and Stefan, 1995;Brissaud et al, 2003;Dahl et al, 2017a,b). Modelling and experimental evidence reported that the combination of thermal stratification and vertically attenuated sunlight in the water column is the cause for greater die-off in the near surface region of the water column during the day (Brissaud et al, 2003;Dahl et al, 2017a,b). This has also generated interest in developing sunlight disinfection models that resolve disinfection in a spatially dependent manner (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…During the operation phases, the daily hydraulic loads were 0.27 and 0.40 m 3 m −2 of sand basin. Alternation of operational and drying periods has always been considered essential to infiltration-percolation and soil aquifer treatment; it is the only practical way to manage clogging at the surface and in the core of filtrating beds (Brissaud et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The hydraulic community has led developments in modelling bacterial concentrations in environmental waters [33] and sewage treatment systems [15,24,37,52,61,63,64,69]. In some notable contributions, the links to defined health outcomes have also been addressed in modelling investigations [31,41,42].…”
Section: Some Preliminariesmentioning
confidence: 99%